Early, structured disease modifying anti-rheumatic drug (DMARD) therapy reduces cardiovascular risk in rheumatoid arthritis--a single centre study using non-biologic drugs - Chatterjee, Sumit; Sarkate, Pankaj; Ghosh, Sudip; Biswas, Monodeep; Ghosh, Alakendu (Journal of the Association of Physicians of India, 2013)
Rheumatoid arthritis, being a chronic disease requires long-term management of patients with drugs. The increasing cost of biologics in this era of disease management led us to devise a treatment regime, optimal for use in a developing country like India, which was economical as well as effective in controlling disease activity. To investigate if combination therapy with DMARDs can reduce cardiovascular risk in early Rheumatoid Arthritis, besides controlling disease activity. A small cohort of early Rheumatoid subjects with disease duration less than 1 year were treated with a structured DMARD regime and were followed up over a year. Disease activity score, C-reactive protein (CRP) and cardiac risk markers like lipid panel and carotid intima-medial thickness were monitored at 6 months and 1 year. A significant reduction (p < 0.001) of disease activity as well as cardiac risk parameters were observed. Our study showed that treatment of early rheumatoid arthritis with a combination regime of traditional DMARDs is highly effective in controlling disease activity as well as cardiovascular risk.